Cultural studies, production et économie morale - Hesmondhalgh, David; Morin, Céline (Réseaux, 2015)
Les approches issues des cultural studies ont insufflé à la recherche sur les productions médiatiques et culturelles une vigueur nouvelle et nécessaire. Cependant, il devient de plus en plus clair au fil des ans qu’elles rencontrent également de sérieuses limites. L’évaluation menée dans cet article repose sur une première partie dans laquelle nous explorons, en profitant du recul historique, la période d’opposition entre les cultural studies et l’économie politique des années 1990, en distinguant ce que nous appelons les modes théorique et populiste des cultural studies. Nous esquissons ensuite les trois « écoles » des approches cultural studies vis-à-vis de la production et de l’économie : cultural economy, production studies, et creative industries analysis. Selon nous, ces approches en cultural studies de la production et de l’industrie dans le domaine de la culture pêchent, tant dans leur mode populiste que dans leur mode théorique, par le manque d’attention portée à des problématiques fondamentales liées à la normativité dans les rapports entre la culture, les médias et l’économie. Dans les deux dernières parties, portant sur le tournant du cultural labour et le concept d’économie morale, nous suggèrerons des solutions pour une prise en compte plus explicite des problèmes de normativité, proposant ainsi une base éthique potentiellement plus rigoureuse pour l’étude de questions importantes dans le champ de la production culturelle. Nous appliquerons succinctement ce système au rapport problématique entre les biens culturels et le bien-être dans les sociétés modernes., ENG: Cultural studies approaches have provided a welcome reinvigoration of research on media and cultural production. But, as the years go by, it becomes clearer that they also suffer from important limitations. To provide a basis for the assessment in this article, the first section revisits the 1990s moment of ‘political economy versus cultural studies’ with the benefit of hindsight, distinguishing what I call the theoretical and populist modes of cultural studies. I then outline three ‘schools’ of cultural studies approaches to production and economy : cultural economy, production studies, and creative industries analysis. My argument is that, in both its theoretical and populist modes, these cultural studies approaches to production and industry in the realm of culture suffer from a lack of attention to fundamental normative issues regarding the relationship between culture, media and economy. In the final two sections, which discuss the turn to cultural labour and the concept of moral economy, I offer suggestions for how key normative issues might be addressed in a more explicit way, potentially offering a more rigorous ethical grounding for important questions regarding the realm of cultural production. I briefly apply this to the problematic relationship between cultural goods and well-being in modern societies.
Communication; Media Studies
Keywords: cultural production; cultural studies; industry; moral economy

Internet, une société contre l’État ? - Loveluck, Benjamin (Réseaux, 2015)
L’informatique en réseau a souvent été présentée comme un instrument favorisant l’auto-organisation de la société civile, à partir de modes alternatifs de distribution du pouvoir et de coordination des activités. L’histoire d’internet, abordée du point de vue de l’histoire des idées, montre que de telles propriétés ont donné lieu à la formation d’une véritable philosophie politique que nous avons appelée le libéralisme informationnel. Celle-ci a vu différents modèles d’économie politique s’affronter ; nous en présentons ici le mouvement général ainsi que les divergences internes. Nous terminons par un exposé de trois grandes formes de gouvernementalité qui en sont issues, et qui ouvrent à une critique de l’économie politique en régime numérique : la captation, la dissémination et l’auto-institution., Network computing has often been presented as an instrument promoting self-organization within civil society, through alternative modes of power distribution and coordination of activities. The history of the Internet, considered from the perspective of the history of ideas, shows that these properties have led to the formation of a genuine political philosophy that we have called informational liberalism. This article presents its overall movement and internal divisions, understood as alternative models of political economy. Finally, three main forms of governmentality stemming from this framework are identified, which pave the way for a critique of political economy in a digital regime : capturing, dissemination and self-institution.
Cultural Studies
Keywords: information society; informational liberalism; internet

Cultures régionales et développement économique dans l'espace rhénan et au-delà - Kahn, René (Revue d'Allemagne et des Pays de Langue Allemande, 2015)
Contemporary economic thought is overwhelmingly dominated by the dogma of the neoclassical school and the Austrian neoliberal school, according to which social organization can fully be understood from two hypotheses: the society can be reduced to its economic aspects, and economic activities are exclusively explained by the utilitarist rationality of individuals. This approach makes unnecessary, at least in the economic sphere, the construction of a collective cultural framework based on preferences and values specific of a "situated" community. Now, many multidisciplinary works confirm the validity of Karl Polanyi's observations and the embedment of cultural aspects in the economic activity, especially within the firms and the territories. This paper discusses the contributions of two collective works: the first book devoted to the Rhine area's model of firm; the second devoted to the relationships between regional cultures and economic development. Based on the literature on this subject, the paper questions the nature of such a model. It also shows how regional cultures succeed to enrich the economic sphere, beyond the methodological individualism, through the construction of a culture of development. (English)
Area Studies
Keywords: Germany; economic theory; embeddedness

Les paiements pour services environnementaux de la Fondation Natura Bolivia entre logiques réciprocitaires, redistributives et marchandes, - Bétrisey, Florence; Mager, Christophe (Revue Française de Socio-Économie, 2015)
La diffusion internationale des paiements pour services environnementaux (PSE) a été interprétée en 2010 par le gouvernement bolivien d’Evo Morales comme une réponse strictement néolibérale à la nécessité d’assurer une gestion durable des ressources naturelles. Supposée amener à terme à l’éviction de toute régulation autre que marchande – qu’elle s’applique à la nature ou aux rapports entre personnes –, la mise en place de PSE n’a pas été encouragée par les autorités nationales boliviennes. Des projets de PSE ont toutefois été lancés, dont les Acuerdos Reciprocos por el Agua (ARA), issus d’un partenariat public-privé dans le département de Santa Cruz. En analysant leur conception et leur fonctionnement au prisme du référentiel polanyien, nous montrons que, contrairement aux craintes gouvernementales, ces PSE ne font pas abstraction des logiques organisationnelles réciprocitaires et redistributives, ajustant au contexte local un objet global., ENG: The international dissemination of payments for ecosystem services (PES) has been interpreted in 2010 by the Bolivian government of Evo Morales as a strictly neo-liberal response to the need to ensure a sustainable management of natural resources. Supposed to contribute to the crowding-out of any other regulation than market – applied to the nature or the relationship between people – the implementation of PES was not encouraged by the Bolivian national authorities. However some PES projects stemming from a public-private partnership have been initiated at local level, as the Acuerdos Reciprocos por el Agua (ARA), in the department of Santa Cruz. Analysing their design and operating through the Polanyian framework, we show that, contrary to the government fears, these PES do not ignore the reciprocal and redistributive organisational logics, adjusting a global object to the local context.
Geography
Keywords: Bolivia; Bolivie; Polanyi; hybridity; hybridité; logique marchande; market logic; paiements pour services environnementaux; payments for ecosystem services; reciprocity; redistribution; réciprocité; sustainable management

Karl Polanyi et l’encastrement politique de l’économie : pour une analyse systémique des rapports changeants entre économie et société, Karl Polanyi and political embeddedness of economy: a systemic analysis of the changing relationships between economy and society - Chochoy, Nicolas (Revue Française de Socio-Économie, 2015)
Cette contribution défend la thèse selon laquelle une interprétation fidèle de l’encastrement au sens de Karl Polanyi nécessite une analyse qui se positionne dans la relation existante entre l’économie et l’institution organisatrice du social. Cette proposition s’étaye sur une analyse systémique des rapports changeants entre économie et société qui éclaire le désencastrement comme processus d’extériorisation du Marché imaginaire autorégulateur. Face à ce processus, l’enjeu d’une économie solidaire nous semble être de créer les conditions d’une réelle auto-organisation démocratique., This paper defends the idea that a faithful interpretation of Karl Polanyi’s embeddedness requires an analysis at the level of the relationships between economy and the institution which organises the social. This proposal is based on a systemic analysis of the changing relationships between economy and society that considers the disembeddedness as an externalisation process of imaginary self-regulating market. In front of this process, the issue of solidarity economy seems to be the creation of conditions for a real democratic self-organisation.
Economics
Keywords: autotranscendance; democracy; démocratie; embeddedness; encastrement; marché; markets; solidarity economy; économie solidaire

La pluralité des logiques d’action de la Banque Palmas au Brésil : entre développement local et partenariats au niveau national, The plurality of Banco Palmas’ strategies: between local development and partnerships at a national level - Meyer, Camille (Revue Française de Socio-Économie, 2015)
Actives dans plus de 100 communautés au Brésil, les banques communautaires de développement représentent un phénomène majeur de l’économie solidaire brésilienne. En se référant aux apports théoriques de Karl Polanyi, cet article propose une analyse des logiques d’action plurielles de la première banque communautaire de développement brésilienne, la Banque Palmas., Effective in more than 100 communities in Brazil, community development banks are a major phenomenon of Brazilian solidarity economy. Referring to the theoretical contributions of Karl Polanyi, this paper proposes an analysis of the plural organizational logics of the first Brazilian community development bank, Banco Palmas.
Economics
Keywords: Brésil; banque communautaire de développement; finances solidaires; social economy; économie plurielle

Le syndicat chinois: Une institution au coeur du rapport salarial. (The Chinese Trade-Union: A Core Institution of the Wage-Earning Relationship. With English summary.) - Perisse, Muriel (Mondes en Developpement, 2015)
The official Chinese Trade Union has gained strength during the reforms, to the point that it must be considered as a central institution of the contemporary Chinese wage ratio. As a quasi-governmental organization, it belongs to the evolutionary institutional design and must find new solutions to the labor problems resulting from the reforms. However, its creativity only produces organizational solutions that are far from achieving a real counter-movement in a Polanyian sense.
Economics
Keywords: countermovement; economic development: human resources; economic integration; human development; income distribution; industry studies; international linkages to development; migration; population; role of international organizations; socialist institutions and their transitions: international trade; finance; investment; relations; and aid P33; socialist systems and transitional economies: factor and product markets; wage differentials; wage level and structure